2012
DOI: 10.3349/ymj.2012.53.4.671
|View full text |Cite
|
Sign up to set email alerts
|

Leptin as a Modulator of Neuroendocrine Function in Humans

Abstract: Leptin, a peptide hormone secreted by adipocytes in proportion of the amount of energy stored in fat, plays a central role in regulating human energy homeostasis. In addition, leptin plays a significant permissive role in the physiological regulation of several neuroendocrine axes, including the hypothalamic-pituitary-gonadal, -thyroid, -growth hormone, and -adrenal axes. Decreased levels of leptin, also known as hypoleptinemia, signal to the brain a state of energy deprivation. Hypoleptinemia can be a congeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 102 publications
(184 reference statements)
1
42
0
Order By: Relevance
“…Elevated corticosterone appears to be a common fi nding in murine models of leptin defi ciency ( 59 ), possibly owing to lack of a direct suppressive effect of leptin on glucocorticoid secretion by corticoadrenal cells ( 60 ). Interestingly, whereas adrenalectomy dramatically improves both hyperglycemia and hyperinsulinemia in A-ZIP/F-1 lipodystrophic mice, it fails to reduce liver triglyceride concentrations in these animals ( 61 ), suggesting that hypercorticosteronemia does not play an essential role in the hepatic steatosis associated with severe lipodystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated corticosterone appears to be a common fi nding in murine models of leptin defi ciency ( 59 ), possibly owing to lack of a direct suppressive effect of leptin on glucocorticoid secretion by corticoadrenal cells ( 60 ). Interestingly, whereas adrenalectomy dramatically improves both hyperglycemia and hyperinsulinemia in A-ZIP/F-1 lipodystrophic mice, it fails to reduce liver triglyceride concentrations in these animals ( 61 ), suggesting that hypercorticosteronemia does not play an essential role in the hepatic steatosis associated with severe lipodystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, leptin is a peptide hormone secreted by adipose tissue which plays a central role in regulating human energy homeostasis (24,25). It has been proven that the level of leptin in blood serum is higher in the obese, in comparison with both adults and children of appropriate body mass.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Few studies have investigated the hormonal changes related to the return of the menstrual cycle [7,12]. Only one study observed the hormonal changes that occur at the time of menstrual cycle return [13], but this study did not emphasize IGF-1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The pulsatile secretion of this hypothalamic peptide accelerates in proportion to the stock of fat; in other words, the excessive loss of adipose tissue leads to the decreased production of leptin, which diminishes signals to the central nervous system, leading to a decrease in GnRH and a subsequent drop in LH and FSH levels. These changes consequently lead to hypogonadotropic hypogonadism [7,8,9]. …”
Section: Introductionmentioning
confidence: 99%